KINERJA ORGANISASI PADA DINAS PERHUBUNGAN, PARIWISATA, KEBUDAYAAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN BLORA - Intan Suryani; Susi Sulandari (Journal of Public Policy and Management Review, 2016)
This research is done to describe the performance of the organization in the Department of Transportation, Tourism, Culture, Communication and Information Blora using organizational performance measurement indicators and the factors that affect organizational performance. Blora has considerable potential to compete with other regions, but the maintenance of tourism destinations, transportation, and communication to the public has less impact on the lack of existence of Blora. This research was done to find out the reach of productivity, responsiveness, outcomes, quality of service, and the use of resource DPPKKI Blora. Researcher also describes the factors that support and obstruct the performance of the organization. This research is kind of descriptive qualitative research, that the data collection techniques through observation, interview, and literature research. Informants were taken by the researcher is head of department, head of the DPPKKI and some Bloras’ societies. In this research, researcher used indicators of organizational performance from Jerry Harbour, Dwiyanto, and the Institute of Public Administration that combined according to problems in the field. The targets are made do not fully reached. The research found that human resources be a big factor in supporting and obstruct the performance of DPPKKI. Another thing, the researcher assume that organizational cultureof DPPKKI affects organizational performance is incoreect, but the results of research in the field of technology which is a factor supporting and obstructing organizational performance. Based on the results of this research concluded that the performance of the organization in the Department of Transportation, Tourism, Culture, Communication and Information Blora is needs to be increased. Recommendations given by the researcher is to increase the amount of human resources, need for education and training in turism and transport, infrastucture and facilities also need to do the filing procurement of renewable techonogies is a data processor.